2012
DOI: 10.1063/1.3687345
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy electron collisions with glycine

Abstract: We report cross sections for elastic electron scattering by gas phase glycine (neutral form), obtained with the Schwinger multichannel method. The present results are the first obtained with a new implementation that combines parallelization with OpenMP directives and pseudopotentials. The position of the well known π* shape resonance ranged from 2.3 eV to 2.8 eV depending on the polarization model and conformer. For the most stable isomer, the present result (2.4 eV) is in fair agreement with electron transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 42 publications
1
44
0
2
Order By: Relevance
“…In the present study, we also employed the Schwinger multichannel method with pseudopotentials (SMCPP) [40][41][42] to obtain theoretical cross sections for the excitation of the previously discussed bands 4 of furfural by electron impact. This theory was recently reviewed in Ref.…”
Section: Analysis Procedures and Theorymentioning
confidence: 99%
“…In the present study, we also employed the Schwinger multichannel method with pseudopotentials (SMCPP) [40][41][42] to obtain theoretical cross sections for the excitation of the previously discussed bands 4 of furfural by electron impact. This theory was recently reviewed in Ref.…”
Section: Analysis Procedures and Theorymentioning
confidence: 99%
“…Though a broad and low-lying resonance with σ * OH character would in principle be expected, we found no clear signature of such a state. As discussed elsewhere [21], this assignment would be difficult in view of the s-wave contribution, the large background, and even the coupling to virtual or dipole-supported states. Inspection of the lowest unoccupied molecular orbitals (LUMOs) obtained with the compact 6-31G(d) basis set, a procedure routinely employed in ETS assignments [29], suggests that a σ * OH resonance would indeed exist (this is also supported by DEA data [28]).…”
mentioning
confidence: 99%
“…This variational approach to the T -matrix was discussed in detail elsewhere [21,22] and relies on a discrete trial set to expand the scattering state. The present calculations were performed in two approximations, namely, static-exchange (SE) and static-exchange plus polarization (SEP).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the DR2013 success of this approach, particularly in description of VFRs, and in spite of the excellent agreement with experiments on formic acid [27], several objections were made with regard to the existence of the * resonance in these systems. Indeed the standard Breit-Wigner parametrization of the scattering eigenphases did not allow for detection of a low-energy * resonance in formic acid [28], uracil [29][30][31] or glycine [32]. Our studies [19,25] showed that the * resonances in these systems at the equilibrium nuclear geometry are extremely broad with the resonance width reaching 5-6 eV, therefore the resonance width actually exceeds the resonance energy.…”
Section: Mechanismsmentioning
confidence: 87%